Role of Wnt/β-catenin pathway in molecular mechanism of tumorigenesis - Lamparska-Przybysz, Monika; Wieczorek, Maciej; Majorek, Maria; Guzenda, Piotr (Contemporary Oncology/Współczesna Onkologia, 2006)
The increasing interest of the scientific community, over the last decade, in the Wnt-dependent signalling pathways is supported by the documented importance of these pathways in a broad range of physiological conditions and disease states. For instance, it has been shown that inappropriate regulation and activation of these pathways is associated with several disorders including cancer, retinopathy, tetra-amelia and arthritis. In addition, several components of the Wnt-dependent signalling pathways appear to play important roles in diseases such as Alzheimer’s disease, schizophrenia and bipolar disorder. Evidence that altered Wnt signalling is important for human tumour development comes from three major findings: 1) the tumour suppressor adenomatous polyposis coli (APC) binds to the Wnt pathway component b-catenin and is involved in its degradation, 2) mutations of APC in colon tumours lead to stabilization of the b-catenin protein and 3) tumour-associated mutations of b-catenin in colorectal cancer as well as in other tumour types lead to its stabilization, qualifying b-catenin as a proto-oncogene. In this review we will describe the biochemical interactions which shape the Wnt pathway and focus on its role in tumorigenesis.